Measurements of dissolved inorganic carbon (DIC) offshore of Ensenada, Baja California, Mexico (IMECOCAL sampling Line 100) from 2008 to 2016 - José Martín Hernández-Ayón; Norma Lidia Oliva-Mendez; José Augusto Valencia-Gasti (PANGAEA, 2025)
The data sets include measurements of dissolved inorganic carbon (DIC, this dataset) and ancillary CTD variables (https://doi.pangaea.de/10.1594/PANGAEA.976184) from cruises conducted offshore of Ensenada, Baja California (Mexico) along Line 100 of the Investigaciones Mexicanas de la Corriente de California (IMECOCAL) program. The hydrographic data was used to estimated pH, calcium carbonate saturation states, and DIC concentrations from 1998 to 2016 based on the algorithms of Alin et al. (2012). The regular IMECOCAL stations of Line 100 are spaced 37 km apart and extend a maximum distance of 220 km offshore. Data columns include sampling date/time stamps in ISO format, longitude, latitude, depth, pressure, temperature, and salinity information obtained from a CTD mounted with a dissolved oxygen (DO) sensor. Data from the DO sensor were calibrated with data from the Niskin bottle samples analyzed with the microWinkler method. A total of 78 DIC measurements were obtained using the coulometric method described by Johnson et al. (1987), while the remaining direct measurements (42 values) used to validate the Alin et al. (2012) estimates were analyzed with an LI-7000 gas analyzer (CO?/H?O, LICOR, Lincoln, NE, USA). In both cases, seawater samples from the Niskin bottles stored in borosilicate bottles were used to determine DIC. Samples were immediately poisoned with 100 mL of a saturated HgCl? solution to inhibit biological changes and sealed with Apiezon grease. Certified reference material (CRM) from Dr. Andrew Dickson extquotesingles laboratory at Scripps Institution of Oceanography (University of California, San Diego) was used to assess the precision and accuracy of measurements. The reference material analysis indicated a relative average difference of ± 3 μmol/kg and uncertainty of 1.5%.